Organocatalytic Atom-Transfer C(sp3)–H Oxidation - Johnson, Shea L.; Combee, Logan A.; Hilinski, Michael K. (Synlett, 2018)
Predictably site-selective catalytic methods for intermolecular C(sp3)–H hydroxylation and amination hold great promise for the synthesis and late-stage modification of complex molecules. Transition-metal catalysis has been the most common approach for early investigations of this type of reaction. In comparison, there are far fewer reports of organocatalytic methods for direct oxygen or nitrogen insertion into C–H bonds. Herein, we provide an overview of early efforts in this area, with particular emphasis on our own recent development of an iminium salt that catalyzes both oxygen and nitrogen insertion.1 Introduction2 Background: C–H Oxidation Capabilities of Heterocyclic Oxidants3 Oxaziridine-Mediated Catalytic Hydroxylation4 Dioxirane-Mediated Catalytic Hydroxylation5 Iminium Salt Catalysis of Hydroxylation and Amination6 Conclusion and Outlook
Keywords: amination; catalysis; chemoselectivity; dioxiranes; insertion